Grafomotricidad y su influencia en el desarrollo de la lectoescritura en los niños de la Unidad Educativa Francisco Huerta Rendón, cantón Babahoyo - Bohórquez Mora, Alissa Brigitte (2023)
This monographic work is located in the Francisco Huerta Rendón Educational Unit. The purpose of this research was to determine from the literature to what extent graphomotor development prior to and during the second year of elementary school affects the learning process of writing. The approach to the problem, under a critical context and analysis, and the formulation of the problem, led to the directional objectives of the research. The use of bibliographical sources to establish the theoretical framework, based on philosophical and legal foundations, and the formulation of topics according to the type of categories included, were a basis for the investigation. Finally, it was found that graphomotor development significantly influences before and during the learning process of writing in second grade children. For this reason, it is essential to apply graphomotor development activities that enhance the writing learning process, since in this way a correct learning process of the writing skill is ensured.